Essays in Literary Aesthetics - Ghosh, Ranjan K. (SpringerBriefs in Philosophy,, 2018)
The book deals with philosophical issues concerning the understanding of the literary text and its distinctive nature, meaning, and relevance to life. It also provides an occasion to revisit many of the seminal ideas towards these ends by contextualizing them in the current ongoing philosophical discourse on art, in general, and literary art, in particular. Some of the questions addressed in this book are: What is a literary text? What do we understand by the concept of intention in the context of literary arts? Are the feelings experienced in a literary text real? What then is the sense of "truth" in literature which is fictional in character? What relevance do moral concerns and perceptions have in appreciation of the literary text? These are some of the seminal questions that are dealt with by critically responding to views of contemporary thinkers. In short, the book makes an attempt to provide a critical overview of contemporary debates and discussions of literary aesthetics mainly from a Western analytical perspective. The author argues that understanding a literary text is not a purely cognitive exercise; on the contrary, we experience aesthetic meaning or truth in terms of valuable insights that play a role in our understanding of life and emotions. This book is useful for scholars, researchers and students of philosophy and literature interested in aesthetics.